2016
DOI: 10.1063/1.4960824
|View full text |Cite
|
Sign up to set email alerts
|

Development of core ion temperature gradients and edge sheared flows in a helicon plasma device investigated by laser induced fluorescence measurements

Abstract: We report experimental observation of ion heating and subsequent development of a prominent ion temperature gradient in the core of a linear magnetized plasma device, and the controlled shear de-correlation experiment. Simultaneously, we also observe the development of strong sheared flows at the edge of the device. Both the ion temperature and the azimuthal velocity profiles are quite flat at low magnetic fields. As the magnetic field is increased, the core ion temperature increases, producing centrally peake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…The axial velocity, v z , was measured by a Mach In previous studies, we found that Mach probe measurements can give spuriously large axial flows 22 which were later found to be inconsistent with laser-induced fluorescence (LIF). 27 This overestimation of parallel Mach number is found to be related to shadowing effects in Mach probes. 30 In this study, we used small enough tips (D probe ≈ 3 mm) to avoid probe shadowing effects and we verified that the mean flow profile measured by the Mach probe agreed with LIF measurements of the same ion flow taken in the same plasma conditions.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The axial velocity, v z , was measured by a Mach In previous studies, we found that Mach probe measurements can give spuriously large axial flows 22 which were later found to be inconsistent with laser-induced fluorescence (LIF). 27 This overestimation of parallel Mach number is found to be related to shadowing effects in Mach probes. 30 In this study, we used small enough tips (D probe ≈ 3 mm) to avoid probe shadowing effects and we verified that the mean flow profile measured by the Mach probe agreed with LIF measurements of the same ion flow taken in the same plasma conditions.…”
Section: Methodsmentioning
confidence: 97%
“…More details on this device can be found in previous publications. 21,22,27 A horizontal scanning probe was used to record basic plasma information such as ion saturation currents and floating potentials at port α that is about 1 m downstream from the helicon source. The probe array is a combination of Mach and Langmuir probes and is capable of measuring the axial and radial plasma velocities simultaneously (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, LIF measurements in CSDX show that the axial flow is well within the subsonic limit. 31 Thus, the radial gradient of the parallel velocity reported as contributing to an inward particle flux in Ref. 32 does not contribute to such a flux here, as a parallel shear flow instability simply cannot be triggered.…”
Section: Structure Of the 3-field Reduced Modelmentioning
confidence: 64%
“…Experimental results show that when drift waves dominate, the turbulence production due to the release of free energy in r n, can excite secondary parallel flows. 22,25,30,38 Theoretical studies also show that both axial and zonal flows are driven by turbulence, particularly by the non-diffusive residual stress in both expressions for hṽ xṽy i and hṽ xṽz i. 21,23,32,39,40 Reference 26 investigates the relation between the axial and azimuthal flows and turbulence, and formulates a new zonal momentum balance theorem for the coupled drift-ion acoustic waves.…”
Section: B the Vorticity Flux The Perpendicular Reynolds Stress Anmentioning
confidence: 99%
“…r as a function of the density fluctuationsñ normalized by the average plasma density n 42 l 0 ' 2:3q 0:6 s L 0:3 n : (38) This suggests that the CSDX turbulent plasma diffusion coefficient scales like…”
Section: A Case Of a Purely Azimuthal Shearmentioning
confidence: 99%